Labour relations and globalisation: an analysis of ethical dilemmas from 'Le Couperet'. (1st July 2013) - Fábio Francisco de Araujo; Patricia Amélia Tomei
Abstract : This aim of this paper is to analyse how changes in labour relations in a globalised and fiercely competitive context confront professionals with ethical dilemmas when dealing with the prevailing new organisational arrangements. The movie Le Couperet ('The Axe') was chosen for the analysis proposed in this study because it provides a view of the world of work and the effects of the predatory competitiveness imposed by global markets. It concludes that a reflection on corporate ethics and how individuals handle ethical dilemmas may constitute a way of combatting the predatory competitiveness imposed by the logic of the 'new deal'.